Polyelectrolyte composite nanofiber membrane prepared by using coaxial double-row electrostatic spinning process and preparation method of polyelectrolyte composite nanofiber membrane
The polyelectrolyte composite nanofiber membrane prepared by coaxial double-row electrospinning utilizes the electrostatic interaction formed by natural polymers with opposite charges, which solves the problems of poor mechanical strength and secondary damage of existing hemostatic materials, and achieves rapid and safe hemostasis and promotes wound healing.
Patent Information
- Application Number
- CN202411499716.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-25
AI Technical Summary
Existing hemostatic materials present challenges in rapidly and safely controlling bleeding from severe wounds or cuts, due to issues such as poor mechanical strength, susceptibility to distal thrombosis, and secondary injury.
Polyelectrolyte composite nanofiber membranes were prepared using a coaxial double-row electrospinning process. The composite nanofiber membranes were prepared using two natural polymers with opposite charges, and a dense network structure was formed through electrostatic interaction, achieving instant physical sealing and adhesion.
It achieves highly efficient hemostasis without the need for toxic solvents, rapidly forms a dense network structure, possesses good biocompatibility and antibacterial properties, promotes wound healing, and is inexpensive and readily available.
Smart Images

Figure CN119265803A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of medical polymer materials, and specifically relates to a polyelectrolyte composite nanofiber membrane prepared by coaxial double-row electrostatic spinning process and a preparation method thereof. The nanofiber raw material is pure natural, has good biocompatibility and high-efficiency hemostatic performance. Background Art
[0002] Acute hemorrhage is one of the biggest causes of death worldwide each year. There is an urgent need for a practical pre-hospital care solution for acute hemorrhage control, especially in war, disaster and accident situations, which is characterized by high clinical demand and great market potential. The rapid and effective application of hemostatic materials in the early stage of rebleeding can prolong the rescue time, thereby reducing the high mortality rate caused by excessive blood loss. However, it is still challenging for most hemostatic materials to quickly and safely control bleeding caused by severe bleeding wounds or cuts. The required hemostatic materials must be designed and developed to achieve rapid and complete hemostasis of massive hemorrhages of both non-compressible (visceral organs) and compressible (femoral artery in thigh), both of which involve fatal bleeding and are the cause of equal consequences.
[0003] So far, various hemostatic products have been reported, such as gelatin sponge (Gelatin ), Chitosan gauze Celox TM ), Inorganic particles embedded in gauze A variety of hemostatic products have been developed and used in clinical practice. However, they each have certain shortcomings: sponges show good shape memory due to their inherent interconnected macroporous structure, but have poor mechanical strength; porous zeolites can cause thermal damage to surrounding tissues, and they are as likely to cause distal thrombosis as hemostatic powders; gauze must be replaced frequently and is prone to adhesion to the wound, causing secondary damage.
[0004] Quaternized chitosan and alginate are both natural high molecular weight polysaccharides with low cost, abundant sources, and good biocompatibility and biodegradability, which make them have broad application prospects in the field of regenerative hemostasis. Nanofibers, due to their large surface area, high porosity, air permeability, and structural characteristics similar to extracellular matrix, can support the adhesion and migration of fibroblasts and promote tissue regeneration during the wound healing process after hemostasis. Summary of the invention
[0005] In order to overcome the technical problems of poor mechanical strength of the above-mentioned hemostatic materials, easy to cause distal thrombosis and easy to cause secondary damage, and to prepare an efficient hemostatic nanofiber auxiliary material that does not require any toxic organic solvents, has good biocompatibility and can interact with groups on the wound, the present invention provides a cross-linking agent, a degradable and efficient hemostatic sponge used for non-pressable wounds. The purpose of the present invention is to provide a polyelectrolyte composite nanofiber membrane prepared by a coaxial double-row electrospinning process and a preparation method thereof. The present invention ingeniously adopts a coaxial double-row electrospinning method to prepare a composite nanofiber membrane hemostatic auxiliary material using two natural high molecular polymers of polyelectrolytes with opposite charges, anions and cations. Only a simple aqueous solution is used as a solvent to dissolve the corresponding components, and no glutaraldehyde is used as a cross-linking agent, or ultraviolet treatment and other steps are required to obtain flexible nanofibers. Because two polyelectrolytes with opposite charges are introduced as the shell layer of the nanofiber, when the nanofiber encounters blood, electrostatic interaction can occur between the two fibers, thereby forming a dense network structure. At the same time, the material and the groups on the tissue can also interact, thereby achieving an adhesion effect. The above two effects can ensure that the nanofiber can immediately and effectively physically block the wound and immediately adhere to it during the hemostasis process.
[0006] The present invention is achieved through the following technical solutions:
[0007] S1, dissolving polyvinyl alcohol in deionized water to obtain solution a;
[0008] S2, dissolving the polyelectrolyte anion in the aqueous solution to obtain solution b;
[0009] S3, dissolving the polyelectrolyte cation in the aqueous solution to obtain solution c;
[0010] S4, using the solution a obtained in step 1 as the core layer of the nanofiber, the solution b obtained in step 2, and the solution c obtained in step 3 as the shell layer of the nanofiber, and performing electrostatic spinning to obtain polyelectrolyte composite nanofibers
[0011] As a preferred solution, in step S1, the polyvinyl alcohol needs to have a certain molecular weight, which is sufficient to be stretched by the electric field to form continuous fibers. In step S1, the degree of polymerization of the polyvinyl alcohol is 4000-100000; the polyvinyl alcohol solution is dissolved in deionized water at 90°C, and the reaction time is 3 hours.
[0012] As a preferred embodiment, the polyelectrolyte anion is one of carboxymethyl chitosan, alginate, hyaluronic acid, and carboxymethyl cellulose, and the alginate is modified alginate; the polyelectrolyte cation is one of chitosan quaternary ammonium salt, chitosan, and hyaluronic acid, and the chitosan quaternary ammonium salt is modified alginate.
[0013] As a preferred embodiment, the added amounts of polyvinyl alcohol, quaternary ammonium chitosan, modified alginate and acetic acid are 5-10%, 0.5-2.5%, 0.5-3% and 50-90% respectively; the added amounts are calculated as the mass percentage of the total mixture of polyvinyl alcohol, quaternary ammonium chitosan, modified alginate and acetic acid.
[0014] As a preferred solution, the degree of substitution of the quaternized chitosan is 80% to 98%, the dissolution time is 8 hours, and the reaction temperature is room temperature.
[0015] As a preferred embodiment, in step S3, the dissolution temperature of the modified alginate is 0-2°C, and the dissolution time is 8 hours.
[0016] As a preferred solution, the spinning temperature of the electrospinning is 37°C, the humidity is 20-30%, the distance between the plates is 20 cm, the voltage is 21 kV, the flow rate of the liquid in the double-row spinning is 0.09 μL / min, and the spinning time is 12 h.
[0017] The polyelectrolyte composite nanofiber hemostatic auxiliary material obtained by the preparation method of the present invention.
[0018] The present invention adopts the above technical solution, and the polyelectrolyte composite nanofiber membrane hemostatic auxiliary material can form a dense network structure by electrostatic interaction when it meets water, and interact with groups on the tissue, thereby completing immediate physical blocking.
[0019] Compared with the prior art, the method of the present invention has the following beneficial effects:
[0020] 1. The nanofiber hemostatic auxiliary material of the present invention does not use any toxic reagents, does not have any harmful substance residues, is safe and harmless to the human body and has no antigenicity.
[0021] 2. The nanofiber membrane hemostatic auxiliary material shown in the present invention has blood thixotropy, can quickly form a dense network structure, and adhere to tissues to physically seal wounds. At the same time, the material has certain antibacterial properties, can effectively inhibit the formation of bacteria, and promote wound healing.
[0022] 3. The raw material cost of the nanofiber membrane hemostatic auxiliary material described in the present invention is low, easy to obtain, the method is simple, and it is environmentally friendly.
[0023] 4. The nanofiber membrane hemostatic auxiliary material of the present invention directly acts on bleeding wounds, is simple and convenient to use, and is easy to store, transport and carry. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a diagram showing the preparation of the polyelectrolyte nanofabric prepared in the present invention.
[0025] Figure 2This is a physical picture of the polyelectrolyte nanofiber hemostatic auxiliary material prepared by the present invention.
[0026] Figure 3 The in vitro coagulation indexes of the polyvinyl alcohol nanofabric prepared in comparative example 1 of the present invention, the quaternized chitosan nanofabric prepared in comparative example 2, the modified alginate nanofabric prepared in comparative example 3, the polyelectrolyte nanofabric prepared in example 4, the medical gauze, and the combat gauze are 71%, 58%, 56%, 8%, 85%, and 79% respectively; the in vitro coagulation index of the polyvinyl alcohol nanofabric prepared in comparative example 1 is 85%, indicating that it does not have a good red blood cell capture ability, that is, it cannot quickly enrich coagulation factors to form thrombus and achieve hemostasis. The numerical values of the polyelectrolyte composite nanofabric prepared by the coaxial double-row electrospinning process show that the nanofabric composed of nanofibers with opposite charges can not only enrich red blood cells and platelets by relying on its own positive charge, but also generate electrostatic interactions after encountering blood, thereby forming a dense network structure, so that the polyelectrolyte nanofabric prepared in example 3 exhibits excellent in vitro coagulation ability.
[0027] Figure 4 The hemostasis of the polyvinyl alcohol nanofabric prepared in comparative example 1 of the present invention, the quaternized chitosan nanofabric prepared in comparative example 2, the modified alginate nanofabric prepared in comparative example 3, the polyelectrolyte nanofabric hemostatic auxiliary material, medical gauze, and combat gauze prepared in embodiment 4 in the rat femoral artery injury model. The polyvinyl alcohol nanofabric prepared in comparative example 1, the quaternized chitosan nanofabric prepared in comparative example 2, and the modified alginate nanofabric prepared in comparative example 3 all showed that they failed to seal the wound well, thereby achieving a hemostatic effect. However, it can be seen from the polyelectrolyte composite nanofabric prepared by the coaxial double-row electrospinning process that the nanofabric composed of nanofibers with opposite charges not only undergoes electrostatic interaction after encountering blood, but also undergoes chemical reaction with tissues, thereby achieving an adhesion effect. Therefore, the polyelectrolyte nanofabric prepared in embodiment 3 has a good hemostatic effect on the femoral artery of rats.
[0028] Figure 5 The hemostasis conditions of the rat liver puncture model wounds of the polyvinyl alcohol nanofabric prepared in comparative example 1 of the present invention, the quaternized chitosan nanofabric prepared in comparative example 2, the modified alginate nanofabric prepared in comparative example 3, the polyelectrolyte nanofabric hemostatic auxiliary material prepared in Example 4, the medical gauze, and the combat gauze. DETAILED DESCRIPTION
[0029] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0030] 1) The "modified sodium alginate" described below in the present invention is prepared by the following method: 1 g of sodium alginate is dissolved in 100 mL of 2-morpholineethanesulfonic acid solution with a pH of 5.5 at a concentration of 0.1 wt %, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and nitrogen-hydroxysuccinimide in a mass ratio of 2:1 are added, and then 0.5 g of dopamine hydrochloride is added and reacted for 4 hours to obtain modified sodium alginate.
[0031] 2) The "quaternized chitosan" described below in the present invention is a commercially available product.
[0032] Example 1
[0033] This embodiment relates to a method for preparing a polyelectrolyte composite nanofiber membrane hemostatic auxiliary material prepared by a coaxial double-row electrospinning process, comprising the following steps:
[0034] 1. Dissolve polyvinyl alcohol in deionized water at 90°C to obtain a solution a with a concentration of 5 wt%;
[0035] 2. Dissolve the quaternized chitosan in an acetic acid aqueous solution to obtain a solution b with a concentration of 2 wt%;
[0036] 3. Dissolving the modified alginate in an aqueous solution to obtain a solution c having a concentration of 2 wt%;
[0037] 4. Use solution a obtained in step 1 as the core layer of the nanofiber, solution b obtained in step 2 and solution c obtained in step 3 as the shell layer of the nanofiber, and perform electrospinning. The spinning temperature of the electrospinning is 37°C, the humidity is 20-30%, the distance between the syringe and the receiver (i.e., between the plates) is 20 cm, the voltage is 21 kV, the flow rate of the liquid in the double-row spinning is 0.09 μL / min, and the spinning time is 12 h to obtain polyelectrolyte composite nanofibers.
[0038] Example 2
[0039] This embodiment relates to a method for preparing a polyelectrolyte composite nanofiber membrane hemostatic auxiliary material prepared by a coaxial double-row electrospinning process, comprising the following steps:
[0040] 1. Dissolve polyvinyl alcohol in deionized water at 90° C. to obtain a solution a with a concentration of 7 wt %;
[0041] 2. Dissolve the quaternized chitosan in an acetic acid aqueous solution to obtain a solution b with a concentration of 2 wt%;
[0042] 3. Dissolving the modified alginate in an aqueous solution to obtain a solution c having a concentration of 2 wt%;
[0043] 4. Use solution a obtained in step 1 as the core layer of the nanofiber, solution b obtained in step 2 and solution c obtained in step 3 as the shell layer of the nanofiber, and perform electrospinning. The spinning temperature of the electrospinning is 37°C, the humidity is 20-30%, the distance between the syringe and the receiver (i.e., between the plates) is 20 cm, the voltage is 21 kV, the flow rate of the liquid in the double-row spinning is 0.09 μL / min, and the spinning time is 12 h to obtain polyelectrolyte composite nanofibers.
[0044] Example 3
[0045] This embodiment relates to a method for preparing a polyelectrolyte composite nanofiber membrane hemostatic auxiliary material prepared by a coaxial double-row electrospinning process, comprising the following steps:
[0046] 1. Dissolve polyvinyl alcohol in deionized water at 90° C. to obtain a solution a with a concentration of 7 wt %;
[0047] 2. Dissolve the quaternized chitosan in an acetic acid aqueous solution to obtain a solution b with a concentration of 2 wt%;
[0048] 3. Dissolving the modified alginate in an aqueous solution to obtain a solution c having a concentration of 2 wt%;
[0049] 4. Use solution a obtained in step 1 as the core layer of the nanofiber, solution b obtained in step 2 and solution c obtained in step 3 as the shell layer of the nanofiber, and perform electrospinning. The spinning temperature of the electrospinning is 37°C, the humidity is 20-30%, the distance between the syringe and the receiver is 20 cm, the voltage is 21 kV, the flow rate of the liquid in the double-row spinning is 0.09 μL / min, and the spinning time is 12 h to obtain polyelectrolyte composite nanofibers.
[0050] Example 4
[0051] This embodiment relates to a method for preparing a polyelectrolyte composite nanofiber membrane hemostatic auxiliary material prepared by a coaxial double-row electrospinning process, comprising the following steps:
[0052] 1. Dissolve polyvinyl alcohol in deionized water at 90° C. to obtain a solution a with a concentration of 7 wt %;
[0053] 2. Dissolve the quaternized chitosan in an acetic acid aqueous solution to obtain a solution b with a concentration of 1 wt%;
[0054] 3. Dissolving the modified alginate in an aqueous solution to obtain a solution c having a concentration of 1 wt%;
[0055] 4. Use solution a obtained in step 1 as the core layer of the nanofiber, solution b obtained in step 2, and solution c obtained in step 3 as the shell layer of the nanofiber, and perform electrospinning. The spinning temperature of the electrospinning is 37°C, the humidity is 20-30%, the distance between the syringe and the receiver is 20 cm, the voltage is 21 kV, the flow rate of the liquid in the double-row spinning is 0.09 μL / min, and the spinning time is 12 h to obtain polyelectrolyte composite nanofibers.
[0056] Comparative Example 1
[0057] At a temperature of 90°C, polyvinyl alcohol was dissolved in deionized water to obtain a solution with a concentration of 7wt%, and electrospinning was performed. The spinning temperature of the electrospinning was 37°C, the humidity was 20-30%, the voltage was 21kV, the flow rate of the liquid was 0.09μL / min, the spinning time was 12h, and a nanofabric containing only polyvinyl alcohol was obtained.
[0058] Comparative Example 2
[0059] At a temperature of 90°C, polyvinyl alcohol was dissolved in deionized water to obtain a solution with a concentration of 7wt%, and at room temperature, modified alginate was dissolved to obtain a solution with a concentration of 2wt%. The two were electrospun at a spinning temperature of 37°C, a humidity of 20-30%, a voltage of 21kV, a liquid flow rate of 0.09μL / min, and a spinning time of 12h to obtain a nanofabric containing polyvinyl alcohol and modified alginate.
[0060] Comparative Example 3
[0061] At a temperature of 90°C, polyvinyl alcohol was dissolved in deionized water to obtain a solution with a concentration of 7wt%, and at room temperature, quaternary ammonium chitosan was dissolved in an acetic acid aqueous solution to obtain a solution with a concentration of 2wt%. The two were electrospun at a spinning temperature of 37°C, a humidity of 20-30%, a voltage of 21kV, a liquid flow rate of 0.09μL / min, and a spinning time of 12h to obtain a nanofabric containing polyvinyl alcohol and quaternary ammonium chitosan.
[0062] Example 5
[0063] This embodiment relates to a hemostatic effect test of a polyelectrolyte composite nanofiber membrane hemostatic auxiliary material prepared by a coaxial double-row electrospinning process, comprising the following steps:
[0064] 1. Inject 1 mL of 10 wt% chloral hydrate into the abdominal cavity of the rat to anesthetize it;
[0065] 2. Create a 1 cm × 0.05 cm injury model on the liver;
[0066] 3. Immediately cover the wound with polyelectrolyte composite nanofiber membrane hemostatic auxiliary materials of known area (respectively prepared in Example 4, Comparative Example 1, Comparative Example 2, and Comparative Example 3), medical gauze, and combat gauze to perform non-pressible model hemostasis in a short period of time;
[0067] 4. After 180 seconds, weigh and calculate the amount of bleeding;
[0068] 5. The hemostatic effects of the gauze in the control group, the combat gauze, the polyvinyl alcohol nanofabric used in comparative example 1, the quaternized chitosan nanofabric used in comparative example 2, the modified alginate nanofabric used in comparative example 3, and the polyelectrolyte composite nanofabric used in example 3 on rat liver were as follows: Figure 5 As shown. Compared with the control group gauze, combat gauze, polyvinyl alcohol nanofabric used in comparative example 1, polyvinyl alcohol and modified alginate nanofabric used in comparative example 2, and nanofabric containing polyvinyl alcohol and quaternized chitosan used in comparative example 3, the hemostatic effect of the polyelectrolyte composite nanofabric used in Example 3 is greatly improved, which can be attributed to the electrostatic interaction between the two polyelectrolyte nanofibers after encountering blood, thereby forming a dense network structure, and having adhesion to tissues, which can physically block the wound in time, enrich coagulation factors, and accelerate the hemostatic process, thereby proving its excellent hemostatic ability on non-pressable wounds.
[0069] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A method for preparing a coaxial double-row polyelectrolyte composite nanofiber hemostatic auxiliary material, comprising the following steps: S1, dissolving polyvinyl alcohol in deionized water to obtain solution a; S2, dissolving the polyelectrolyte anion in the aqueous solution to obtain solution b; S3, dissolving the polyelectrolyte cation in the aqueous solution to obtain solution c; S4, using the solution a obtained in step 1 as the core layer of the nanofiber, and the solution b obtained in step 2 and the solution c obtained in step 3 as the shell layer of the nanofiber, and performing electrostatic spinning to obtain polyelectrolyte composite nanofibers.
2. The method for preparing the polyelectrolyte composite nanofiber hemostatic auxiliary material according to claim 1, wherein: The polyelectrolyte anion is one of carboxymethyl chitosan, alginate, hyaluronic acid and carboxymethyl cellulose, and the alginate is modified alginate; the polyelectrolyte cation is one of chitosan quaternary ammonium salt, chitosan and hyaluronic acid, and the chitosan quaternary ammonium salt is modified alginate.
3. The method for preparing a polyelectrolyte composite nanofiber hemostatic adjuvant according to claim 2 is characterized in that the added amounts of polyvinyl alcohol, quaternary ammonium chitosan, modified alginate, and acetic acid are 5-10%, 0.5-2.5%, 0.5-3%, and 50-90%, respectively; the added amounts are calculated as a percentage by mass of the total mixture of polyvinyl alcohol, quaternary ammonium chitosan, modified alginate, and acetic acid.
4. The method for preparing the polyelectrolyte composite nanofiber hemostatic auxiliary material according to claim 1, wherein the dissolution time of solution b and solution c is 8 h.
5. The method for preparing the polyelectrolyte composite nanofiber hemostatic auxiliary material according to claim 1, wherein the polyvinyl alcohol solution is dissolved in deionized water at 90°C and the reaction time is 3 hours.
6. The method for preparing a polyelectrolyte composite nanofiber hemostatic auxiliary material according to claim 1 is characterized in that the spinning temperature of the electrospinning is 37°C, the humidity is 20-30%, the distance between the plates is 20 cm, the voltage is 21 kV, the flow rate of the liquid in the double-row spinning is 0.09 µL / min, and the spinning time is 12 h.
7. The polyelectrolyte composite nanofiber hemostatic adjuvant obtained by the preparation method according to any one of claims 1 to 6.
Citation Information
Patent Citations
Method for preparing bipolar membrane using modified sodium alginate-sodium carboxymethylcellulose as middle interface layer
CN102352543A
Chitosan / sodium alginate / polyvinyl alcohol polyelectrolyte nanofiber composite membrane and preparation method thereof
CN109537163A
Multifunctional medical material as well as preparation method and application thereof
CN115613219A
Method for preparing Anti-adhesion membrane by electrostatic spinning
WO2024216680A1